Photoinitiator-free photopolymerization of silicon-containing maleimides based on electron-donor-acceptor systems - Ahn, Kwang-Duk; Kang, Jong-Hee; Yoo, Kynug Wook; Choo, Dong Joon (MACROMOLECULAR SYMPOSIA, 2007)
Photocured coatings promise enhanced performance, higher productivity and an improved environmental impact on the favorable reduction or near elimination of volatile organic compounds. Increasing interest in the photocuring industry has been imposed on the "photoinitiator-free photo polymerization [PIFP]" system based on the electron-donor-acceptor [EDA] concept, which commonly employs a mixture of a vinyl ether monomer (donor) and an N-substituted maleimide or bismaleimide monomer (acceptor). The PIFP systems employing silicon-containing maleimides together with vinyl ether monomers were firstly investigated and their photoreactions resulted in quite fast curing comparable to the conventional acrylatebased photocurable systems.